PATHOPHYSIOLOGICAL FEATURES OF CREATION OF CRYOPRECYPITATE IN PATIENTS WITH INOPERABLE CANCER IN DISTURBANCES FROM MICROSATELLITE INSTABILITY - О.V. Movсhan; A.V. Titkova (Проблеми екології та медицини)
The study of the mechanisms of pathophysiological patterns of microsatellite illness in patients with inoperable stomach cancer will improve early diagnosis and improve the ways of correction of the revealed violations. The purpose of the work was to identify the pathophysiological patterns of the formation of cryoprecipitate in patients with inoperable gastric cancer, depending on the microsatellite instability (MSI). Blood serum was examined in 70 patients who received a comprehensive treatment for gastric cancer. The diagnosis of all patients is verified histologically; the prevalence of the process was revealed after performing CT scan with intravenous contrast. The isolation of cryoglobulins from blood serum was performed using A.E. Kalovidoris with modifications. In patients with inoperable gastric cancer, with the presence of instability of microsatellites in the locus of VAT-25 and / or VAT-26, the use of fluorouracil was more effective in patients with cryoprecipitate levels of 298.6±2.5 mg / l, while the index was higher than 477,3 mg / L, indicated a low level of efficiency.